When pray is singing, when singing is pray: educational trajectory of a Collective of Singing and Playing in the Kilombola Rural Education - Valéria da Cruz Viana Labrea; Daisy Regina de Souza Reis (Universidade Federal do Norte do Tocantins, 2021)
This article presents the description and analysis of a cartographic research for the construction of a prayer song sung in the terreiro in praise of the Orixás. The cartography (Deleuze & Guatari, 1995) is an "intervention-research" (Kastrup et al, 2015) that allowed us to collectively organize the research songbook When pray is singing, when singing is pray as a map, though partial, of cultural events taking place in the Kilombola community Morada da Paz, at the same time that it allowed us to deepen in the popular Brazilian music to get to know songs that have as their theme the praise of the Orixás. As a result of this research, in addition of a cancioneiro that was presented in different educational spaces for three years, we organized workshops with themes related to education for ethnic-racial relations, rural education and Kilombola education. We relate these contents to a proposal for education in the Kilombola field, based on the articulation of the pedagogy of the landless movement (Caldart, 2000) to the Kilombola education guidelines, education for ethnic-racial relations and enchantment pedagogy.